Optimizing Educational Facilities and Infrastructure for Enhanced Learning at Jeneponto State Islamic Senior High School - Nasir Nasir (Jurnal Edukasi Terkini, 2025)
Purpose-This study aims to explore how managing educational facilities and infrastructure helps improve the quality of education at MAN Jeneponto. Proper management is important because it affects the learning process and the achievement of educational goals. Research Methodology / Design / Approach- The study uses a descriptive qualitative approach. Data were collected through direct observation, interviews with the Principal, Deputy Head of Facilities and Infrastructure, and teachers, as well as related documents. The data were analyzed by reducing information, organizing it systematically, and drawing conclusions based on the findings. Findings-This study found that the management of facilities and infrastructure at MAN Jeneponto follows proper procedures, including planning, procurement, distribution, asset inventory, maintenance, and disposal of unusable items. The school’s education quality is considered very good based on eight national education standards. However, limited funding is a major challenge in managing facilities and infrastructure. Originality and Value-This study highlights the importance of managing infrastructure as a key factor in improving education quality at state religious high schools like MAN Jeneponto. The findings can guide other institutions to better manage their physical resources to support teaching and learning, even with budget limitations.